2023
DOI: 10.1002/fsn3.3201
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinoacetic acid in human nutrition: Beyond creatine synthesis

Abstract: Guanidinoacetic acid (GAA) is a nutrient that has been used in human nutrition since the early 1950s. Recommended for its role in creatine biosynthesis, GAA demonstrated beneficial energy‐boosting effects in various clinical conditions. Dietary GAA has also been suggested to trigger several creatine‐independent mechanisms. Besides acting as a direct precursor of high‐energy phosphagen creatine, dietary GAA is suggested to reduce blood glucose concentration by acting as an insulinotropic food compound, spare am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Additionally, several studies have assessed the metabolic and clinical effects of GAA and found that supplemental GAA does not significantly affect biomarkers of liver damage. 27,43,44 Therefore, further investigations are needed to explain the relationship between GAA and hepatic steatosis. Apart from that, here, it was found that the HFD disrupted lipid and cholesterol metabolism in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies have assessed the metabolic and clinical effects of GAA and found that supplemental GAA does not significantly affect biomarkers of liver damage. 27,43,44 Therefore, further investigations are needed to explain the relationship between GAA and hepatic steatosis. Apart from that, here, it was found that the HFD disrupted lipid and cholesterol metabolism in mice.…”
Section: Discussionmentioning
confidence: 99%
“…These sources include red meat, poultry, milk, and a few plant-based foods. 27 Therefore, dietary supplementation of GAA may influence the hepatic metabolic process via creatine. Previous studies have demonstrated that creatine exerts a negative regulatory effect on adipogenesis during early differentiation by inhibiting the phosphatidylinositol 3-kinase (PI3K) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Guanidinoacetic acid (GAA) is an amino acid derivative and endogenous substance in body tissues [ 1 , 2 ]. GAA acts as an immediate precursor for creatine, which plays a key role in energy metabolism, especially in muscle [ 3 ] and brain [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guanidinoacetate N-methyltransferase (GAMT) is an enzyme that functions to create creatine (Cr), a substance used in the body to transfer and contain energy in the form of phosphate [1] . The process of creatine generation begins with the amino acids glycine and L-arginine.…”
Section: Introductionmentioning
confidence: 99%
“…The process of creatine generation begins with the amino acids glycine and L-arginine. These substrates are trans-aminated to create guanidinoacetic acid (GAA) using the enzyme L-arginine:glycine amidinotransferase (AGAT), after which GAA is transported to the liver or other tissues where GAMT uses S-adenosyl-L-methionine to add a methyl group to form creatine [ 1 , 2 ]. Creatine Kinase (CK) is then used to create phosphocreatine (PCr) which functions as an excellent energy storage source for the formation of adenosine triphosphate (ATP), both of which are used in muscle activity and exercise [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%